Beyond Conflict: Long-Term Labour Market Integration of Internally Displaced Persons in Post-Socialist Countries - Artjoms Ivlevs; Michail Veliziotis (Institute of Labor Economics (IZA), 2017)
The break-ups of the former Soviet Union and Yugoslavia were accompanied by some of the worst military conflicts in modern history, claiming lives of thousands of people and forcibly displacing millions. We study how people displaced by war and conflict within these countries fare on the labour market in the long term – 10 to 15 years after their displacement. Our conceptual framework draws on the theory of cumulative disadvantage and the notion of unemployment 'scarring'. Data come from the Life in Transition II survey, conducted in post-conflict, post-socialist countries in 2010 (n=10,328). Multiple regression analysis reveals a significant long-term labour market disadvantage of forced displacement: people who fled conflict 10-15 years ago are more likely to be long-term unemployed, experience a recent job loss and work informally. We also find that people affected by conflict (both displaced and non-displaced) are more willing to acquire further education and training. These results are not uniform across demographic groups: displaced women consistently experience a greater labour market disadvantage than displaced men, and people affected by conflict in the younger age group (18-34) are particularly keen to acquire extra education and training. Overall, our results highlight a long-lasting vulnerability of the forcibly displaced in developing and transition economies, and advance the emerging literature on the effects of internal displacement on labour market outcomes and human capital accumulation. We also discuss how forced internal displacement extends the theory of cumulative disadvantage.
Keywords: D74; J64; M53; 330; internally displaced persons; post-socialist countries; conflict; labour market outcomes; education; cumulative disadvantage